The social and political realities reflected in Hiligaynon Komiks (1998-2000). - Factuar, Rainier G.
This study is about the social and political realities reflected in Hiligaynon komiks. The study focuses on the two-page Hiligaynon komiks found in Hiligaynon magazine from 1998 to 2000. This study aims, namely: (1) to identify the social and political realities reflected in the selections; (2) to determine the prevalent social and political realities found in the selections; (3) to discuss the realities found in the komiks; and, (4) to show whether the komiks reflect the socail and political reality of the time., This study tells us how media, specifically the komiks, reflect social reality in its contemporary society using the Cone Effect Theory by Edward Jay Whetmore. In this descriptive study, the researchers devised a score sheet that contains the specific categories that the themes of the stories would belong to. Results show that themes on Social realities such as poverty, crime, and values, as well as themes on Political realities such as graft and corruption and Constitutional changes are reflected in the selections. 91.67 percent or 77 out of 84 stories have themes on values, including stories on family relations, social ideals and morals, and love. There is also a great difference of 83.34 percent between the themes on Social realities and Political realities, which shows that focus of the selections is on social issues despite the pertinent political issues during its contemporary time. Also,the selections indeed reflect the real social situation of the 1998 to 2000 Philippine society; however, the real political situation was not given much focus as it only had seven out of 84 stories or 8.33 percent despite the fact that the country was in political turmoil. This suggests that the selections would like us to focus on our social roles and values as these are the foundations of leadership and governance. The researchers recommend that further study on another time frame or era should be done to know what social realities are present in the selections in different periods.